Deoxyribonucleic Acid Hybridization Analysis of the Defective Bacteriophage Carried by Strain 15 of Escherichia coli - Grady, Leo J. (1971)
Evidence from several laboratories indicates that strain 15 of Escherichia coli is lysogenic for a defective phage. When lysates from induced cultures were centrifuged in CsCl, three bands were obtained. In order of decreasing density, these bands contained tailless particles, complete phages, and a second band of complete phages, in a ratio of 65.7:28.6:5.7. Reassociation rate measurements were used to establish that the molecular weights of the deoxyribonucleic acid (DNA) species from the phages in the first two bands are similar. A smaller genome is postulated in the complete phages from the minor band. Hybridization experiments revealed extensive homology between the DNA species from all three phage bands, thus suggesting that the complete and tailless particles are not different at the genetic level. The DNA from each phage band was also shown to hybridize almost completely with DNA from either E. coli 15T(−) or a reportedly cured derivative of 15T(−). In contrast, only about 25% of each phage DNA was able to react with DNA from E. coli strains B and K-12 C-600.